2019
DOI: 10.1111/ijfs.14369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil droplet size on the oxidative stability of the free and encapsulated fractions of freeze‐dried microencapsulated sunflower oil

Abstract: This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving. effective as oxygen barriers, a reduction of the ODS of the parent emulsion by an increase in the homogenisation pressure will result in capsules more stable against lipid oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Likewise, the results in Figure 2 also suggest that oxidation was faster in the oils encapsulated with matrix B (note the different concentration scales), which would be in agreement with the results found for the initial samples. These results are also coherent with those obtained in a recent report, in which the same encapsulation matrices as those used in the present work were studied (Holgado et al, 2020). It was found that an encapsulation matrix constituted by sodium caseinate and D-lactose, named matrix A in the present study, provided greater protection against lipid oxidation than a matrix formed with gelatin, maltodextrin (10 DE) and sucrose, referred to as matrix B in the present work.…”
Section: Detection Of Radicals During Late Oxidationsupporting
confidence: 93%
See 3 more Smart Citations
“…Likewise, the results in Figure 2 also suggest that oxidation was faster in the oils encapsulated with matrix B (note the different concentration scales), which would be in agreement with the results found for the initial samples. These results are also coherent with those obtained in a recent report, in which the same encapsulation matrices as those used in the present work were studied (Holgado et al, 2020). It was found that an encapsulation matrix constituted by sodium caseinate and D-lactose, named matrix A in the present study, provided greater protection against lipid oxidation than a matrix formed with gelatin, maltodextrin (10 DE) and sucrose, referred to as matrix B in the present work.…”
Section: Detection Of Radicals During Late Oxidationsupporting
confidence: 93%
“…The DMO compositions expressed in w/w were respectively 25% oil, 35% caseinate and 40% Dlactose (matrix A); and 25% oil, 5% gelatin, 25% maltodextrin and 45% sucrose (matrix B). The elaboration conditions were those used in a previous study (Holgado et al, 2020) with the exception of the emulsification step. The coarse emulsions were also prepared in a DI-25…”
Section: Dried Microencapsulated Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are relevant for the spray‐drying process because uniform droplets with small sizes are required to achieve high microencapsulation efficiency. [ 10,41,42 ]…”
Section: Resultsmentioning
confidence: 99%